IKLIM KOMUNIKASI ORGANISASI DALAM MENINGKATKAN KINERJA KARYAWAN GORES DIGITAL - Mirna Wati, Dewa Ayu; Suniantara, I Ketut Putu (UHN IGB Sugriwa Denpasar, 2024)
Organizational communication climate is a combination of perceptions regarding communication events, communication behavior, employee responses to other employees, expectations, interpersonal conflicts and opportunities for growth in the organization. The importance of the existence of a communication climate led Kompelmen, Brief and Guzoo to create a hypothesis stating that changes in an organization's communication climate might affect employee performance and productivity. Gores Digital is a start-up company engaged in printing technology (Printech) which helps solve the problems of customers who want a fast, easy and efficient printing process. Gores Digital as a company must have a good organizational communication climate. With a good communication climate, Gores Digital employees can complete it well. Changes in the organizational communication climate will later affect employee productivity or performance because employee performance measures become the main focus in achieving company goals. The research method used is a qualitative method. The aim of this research is to determine whether there is an influence of organizational communication climate on the performance of Gores Digital employees